Pengaruh Ekuitas Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Kosmetik Wardah (Survei Pada Mahasiswi Administrasi Bisnis Angkatan 2016-2018 Universitas Mulawarman, Samarinda) - IIS NURLAILA (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims: (i) to find out the Brand Equity and Product Quality variables simultaneously have a significant effect on purchasing decision (ii) To find out the Brand equity and product quality variables partially have a significant effect on purchasing decision (iii) To find out between the brand equity product quality variable that most influence on costumer purchasing decision at business administration class 2016-2018, social science and politics faculty of Mulawarman University, Samarinda. This study uses tree variables namely the brand equity, product quality and purchasing decision. This type of research is a correlation method with a quantitative approach. The populations in this research were all business administration class 2016-2018 social Science and politics faculty of Mulawarman University, Samarinda with 81 respondents as research samples and the sampling technique used non-probability sampling with saturation sampling method. Data collection techniques: field research (questionnaires, documentation) and library research. Then the analysis technique used is multiple linear regression using the test: validity test, reability test, classic assumption test (normality test, multicollinearity, heteroscedasticity), hypothesis test (partial, simultaneous, dominant), multiple linear regression analysis. The result obtained in this study are (i) brand equity and product quality simultaneously had a significant effect on purchasing decision, (ii) Brand equity and Product quality partially had a significant effect on purchasing decision (iii) Product quality is a variable that has the most influence on consumer purchasing decision at business administration class 2016-2018, social Science and politics faculty of Mulawarman University, Samarinda